2016
DOI: 10.18632/oncotarget.12112
|View full text |Cite
|
Sign up to set email alerts
|

BIM deletion polymorphisms in Hispanic patients with non-small cell lung cancer carriers of EGFR mutations

Abstract: Background: Germline alterations in the proapoptotic protein Bcl-2-like 11 (BIM) can have a crucial role in diverse tumors. To determine the clinical utility of detecting BIM deletion polymorphisms (par4226 bp/ par363 bp) in EGFR positive non-smallcell lung cancer (NSCLC) we examined the outcomes of patients with and without BIM alterations.Results: BIM deletion was present in 14 patients (15.7%). There were no significant differences between patients with and without BIM-del in clinical characteristics or EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…In contrast, Bim downregulation following siRNA transfection delayed paclitaxel-induced apoptosis, suggesting that low expression of Bim is responsible for paclitaxel-resistance in cancer cells (52). It has also been demonstrated that Bim deletion polymorphisms are associated with a poor clinical response to erlotinib and may be an independent prognostic factor for patients with non-small cell lung cancer with the EGFR mutation (53,54). Collectively, these previous studies suggest that many chemotherapeutic agents use Bim to trigger apoptosis in a variety of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Bim downregulation following siRNA transfection delayed paclitaxel-induced apoptosis, suggesting that low expression of Bim is responsible for paclitaxel-resistance in cancer cells (52). It has also been demonstrated that Bim deletion polymorphisms are associated with a poor clinical response to erlotinib and may be an independent prognostic factor for patients with non-small cell lung cancer with the EGFR mutation (53,54). Collectively, these previous studies suggest that many chemotherapeutic agents use Bim to trigger apoptosis in a variety of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In East Asians, but not Caucasians or Africans, a 2,903-bp deletion polymorphism in the BIM gene was found to be present at incidences of around 13% and 0.5% for heterozygous and homozygous carriers, respectively (10). Another study has recently reported that 15.7% of hispanic patients with NSCLC carried the deletion allele (11). Importantly, the BIM deletion polymorphism results in the preferential splicing of exon 3 over the BH3-encoding exon 4 in the BIM pre-mRNA, and leads to the production of inactive BIM isoforms lacking the BH3 domain.…”
Section: Introductionmentioning
confidence: 98%
“…It has previously been demonstrated that Bim is essential for EGFR-TKI-induced killing of NScLc cells (14). A recent study further demonstrated that a common Bim deletion polymorphism contributes to poor responses among NScLc patients with EGFR-mutations treated with EGFR-TKIs (15). Patients with this polymorphism were shown to have a reduced median progression-free survival (mPFS; 6.6 vs. 11.9 months, respectively; P=0.003) (16).…”
Section: Introductionmentioning
confidence: 97%